2021
DOI: 10.3389/fonc.2021.659380
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Efficacy and Safety of Anlotinib With and Without Immunotherapy in Advanced Non-Small Cell Lung Cancer

Abstract: AimsCombination of anti-angiogenesis therapy and immunotherapy has showed synergistic effects in non-small cell lung cancer (NSCLC). The aim of this retrospective study was to investigate the efficacy and safety of anlotinib with and without immunotherapy in NSCLC.MethodsPathologically confirmed NSCLC patients (stage IIIB-IV) receiving anlotinib between November 2018 and February 2020 were enrolled for retrospective analysis. The outcomes and safety of overall patients were evaluated, and the efficacies of anl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
1
18
1
Order By: Relevance
“…In addition, only two patients off treatment due to oral mucositis. Compared to the AEs associated with anlotinib and immunotherapy reported in previous studies, 23 , 42 no new AEs were observed in the present study. Our results show that anlotinib and immunotherapy is well tolerated in patients with the locally advanced NSCLC.…”
Section: Discussioncontrasting
confidence: 81%
“…In addition, only two patients off treatment due to oral mucositis. Compared to the AEs associated with anlotinib and immunotherapy reported in previous studies, 23 , 42 no new AEs were observed in the present study. Our results show that anlotinib and immunotherapy is well tolerated in patients with the locally advanced NSCLC.…”
Section: Discussioncontrasting
confidence: 81%
“…Consistent with our findings, the researchers also found that combination of anlotinib and immunotherapy were most noticeable in patients with wild-type EGFR. [21] In line with this, we speculated that more advanced NSCLC patients without EGFR mutation may have survival benefit from this combination therapy, but more samples need to be enrolled and analyzed.…”
Section: Discussion:mentioning
confidence: 88%
“… 30 , 31 In addition, anlotinib has been shown to have synergistic effects with chemotherapy and targeted therapies. 32 , 33 Adverse effects of anlotinib monotherapy have been shown to be manageable in previous studies. 34–36 Based on the ALTER0303 study, anlotinib has been approved as an NSCLC standard third-line treatment indication.…”
Section: Discussionmentioning
confidence: 98%